A retrospective chart audit of electroconvulsive therapy at a regional Australian hospital. (October 2016) - Stormont, Barry; Diedricks, Angelo A; Kidd, Garry
Objectives: The objective of the current study was to provide a contemporary review of electroconvulsive therapy (ECT) practice in Far North Queensland, Australia. Method: Demographic, diagnostic and treatment characteristics were extracted from the hospital files of people who received ECT between 2011 and 2013. Data were quantitatively analysed and described. Results: Depressive illnesses were the most common indicator for treatment. However, psychotic illnesses also made up a large proportion of treated cases. The technical aspects of treatment were commensurate with previous Australian findings except for the higher incidence of bifrontal ECT and maintenance treatment. Conclusions: Further research is needed across Australia to determine whether the findings of the current study represent changes in Australian ECT practice.